Consumo, comportamento e desempenho de potros recém-desmamados submetidos a dietas com diferentes fontes de volumosos conservados - Pamella Grossi de Sousa (2023)
The objective was to evaluate dry matter intake, nutrient intake, behavior and performance of weaned foals receiving different sources of preserved roughage. Twenty newly weaned foals of the Mangalarga Marchador breed, with an average age of 6 months and 135.9±29.4kg of body weight, participated in the experiment. The experimental period lasted 110 days, and the first 35 days were for adaptation. The foals were divided into 4 groups: corn silage (CS), conventional Tifton 85 hay (HAY), pelletized Tifton 85 hay (PELET) and pre-dried Tifton 85 silage (PS). The diets were formulated to meet the requirements of the category and were isoproteic and isoenergetic. Seven evaluations (A1 to A7) of forage dry matter intake (FDMI) day and night, total dry matter intake (TDMI) and nutrient intake were carried out. The ingestive behavior and FDMI of ten foals were also evaluated in an automated way in the Intergado® trough called FDMIi. Behavioral assessments were performed at the START and END of the study through visual observations at five-minute intervals for 24 hours. Body weight (BW), body condition score (BCS), withers height, rump height and width and daily weight gain (DWG) of twenty foals were evaluated on days 1 (D1), 28 (D28), 59 (D59) and 75 (D75) of the experimental period. Intake, behavior and performance results were analyzed in a randomized block design (RBD) with split plots and the results recorded by the Intergado® electronic trough were analyzed in RBD and the means compared by Tukey's test at 5% significance. The HAY and PELET treatments did not differ (p>0.05) regarding IMSF nutrient consumption, but there was a difference (p<0.05) in the consumption of nitrogen bound to acid detergent fiber (NADF), ether extract (EE), calcium (Ca) and magnesium (Mg). PS provided lower (p<0.05) nutrient intake than HAY and PELET due to lower (p<0.05) FDMI. The distribution of day and night FDMI represented on average 45% and 55%, respectively, for HAY, PS and CS treatments and 35% and 65%, respectively, for PELET treatment. The CS treatment provided the lowest IMS of forage and total, crude protein and fiber and the highest consumption of non-fiber carbohydrates from high starch consumption. None of the treatments were able to supply the daily needs of calcium and phosphorus only with roughage. However, CS promoted lower consumption of minerals (p<0.05), especially calcium and phosphorus (90% below the requirement), which can result in orthopedic problems in this category. The manually measured FDMI results corroborate the data recorded by the Intergado® trough, in which the highest IMSFi was for the HAY treatment, followed by the PELET and PS treatments and the lowest was for the CS treatment. Regarding behavior, at the START of the experiment, the CS and PELET treatments provided the shortest times consuming roughage, the longest time standing idle and the longest time performing stereotypies. And in the END, the same treatments provided the shortest times in social interaction and the longest times performing stereotypies. And PELET continued to be the treatment with less time consuming roughage. Regarding performance, there was no difference (p>0.05) between treatments for the variables BW, BCS, height at withers, height and width of rump. However, an average of 50% less DWG was observed in the CS treatment compared to the other treatments during the experiment, except on D28. It was concluded that the consumption and performance of foals was satisfactory in balanced diets with sources of roughage: conventional Tifton 85 hay, pre-dried Tifton 85 silage and pelletized Tifton 85 hay. Despite the promising results, pelleted hay should be used with caution in ad libitum consumption due to the imminent risk of stereotypies and digestive disorders. Corn silage should not be used as a roughage base in diets for newly weaned foals, with direct damage to nutrient intake, performance, behavior, and especially the health of the gastrointestinal tract.